Subglacial hydrological connectivity within the Byrd Glacier catchment, East Antarctica. Issue 220 (2014) - Wright, A.P.; Young, D.A.; Bamber, J.L.; Dowdeswell, J.A.; Payne, A.J.; Blankenship, D.D.; Siegert, M.J.
Abstract: Ice, Cloud and land Elevation Satellite (ICESat) repeat-track laser altimetry has identified 17 sites within the Byrd Glacier catchment, East Antarctica, where rapid ice-surface height changes have occurred, which have been interpreted as evidence for 'active' subglacial lakes. Here we present evidence from a new radio-echo sounding (RES) survey at 11 of these locations to understand the bed conditions associated with the proposed hydrological activity. At none of the sites examined did we find evidence in support of substantial pooled basal water. In the majority of cases, along-track RES bed reflection amplitudes either side of the locations of surface height change are indistinguishable from those within the features. These results indicate that, in most cases, hypothesized 'active' lakes are not discrete radar targets and are therefore much smaller than the areas of surface height change. In addition, we have identified three new relatively large subglacial lakes upstream of the region where most 'active' subglacial lakes are found, in an area where the hydraulic gradient is significantly lower. Our results suggest that substantial and long-lasting basal water storage in the Byrd Glacier catchment occurs only under low hydraulic gradients, while coast-proximal sites of hydraulic activity likely involve small or temporary accumulations of basal water.